2018
DOI: 10.1111/ecog.04008
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of the double mutualism phenomenon

Abstract: A double mutualism (DM) occurs when two interacting species benefit each other in two different functions, e.g. when an animal species acts both as pollinator and seed disperser of the same plant. Besides the double benefit, a DM also imposes a larger risk to both functions if the performance of one partner declines. We conducted the first global review of DMs involving pollinators and seed dispersers, aiming to: 1) assess their prevalence across ecosystems and biogeographical regions; 2) identify the main pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Our study provides evidence that this plant–lizard relationship constitutes one of the five pollination/seed dispersal double mutualisms found around the World between an animal and a gymnosperm (Fuster et al 2018), besides representing the first double mutualism reported in the Mediterranean region. Although E. fragilis shows to be mainly pollinated by wind, we found that lizards, while obtaining energy resources from this gymnosperm, they are relevant for its reproduction as they (i) transport large amounts of pollen from male to female cones when feeding on pollination drops, (ii) increase the germination of light seeds and (iii) act as their main seed dispersers, at least on Dragonera Island (Rodríguez-Pérez et al 2012; Neghme et al 2017; this study).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Our study provides evidence that this plant–lizard relationship constitutes one of the five pollination/seed dispersal double mutualisms found around the World between an animal and a gymnosperm (Fuster et al 2018), besides representing the first double mutualism reported in the Mediterranean region. Although E. fragilis shows to be mainly pollinated by wind, we found that lizards, while obtaining energy resources from this gymnosperm, they are relevant for its reproduction as they (i) transport large amounts of pollen from male to female cones when feeding on pollination drops, (ii) increase the germination of light seeds and (iii) act as their main seed dispersers, at least on Dragonera Island (Rodríguez-Pérez et al 2012; Neghme et al 2017; this study).…”
Section: Discussionmentioning
confidence: 56%
“…Soriano and Ruiz 2002; Kelly et al 2004; Hansen and Müller 2009a; García et al 2012). Such phenomenon is known as ‘double mutualism’ (Hansen and Müller 2009a) and it appears to be especially frequent on island ecosystems, although a number of reports are also from mainland areas (Fuster et al 2018). One likely reason for the major prevalence of double mutualism on islands is the presence of species that compensate their densities, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting extension of our work would be to synthesize population dynamic behavior for "double mutualisms," in which there are two mechanisms of mutualistic benefit to a partner (Fuster et al 2019). Double mutualisms may play important ecological roles in ecosystems with limited resources, such as islands.…”
Section: Applying Our Modelsmentioning
confidence: 99%